PERCEPTION OF NURSING STUDENTS TOWARD NATURAL DISASTER MANAGEMENT: A DESCRIPTIVE STUDY IN PADANG CITY - Mailani, Fitri; Fatin, Atikah; Simandalahi, Tiurmaida (Fakultas Keperawatan Institut Kesehatan Deli Husada, 2025)
Understanding nursing students’ perceptions of natural disaster management is essential to assess their preparedness for potential disasters in their environment. This study aimed to examine the perceptions of nursing students in Padang City regarding natural disaster management. A descriptive survey design was employed, utilizing proportional random sampling, with 288 respondents from Andalas University, Mercubaktijaya University, Alifah Padang University, and Syedza Saintika University, between March and April 2025. Data were collected using a demographic questionnaire and the Disaster Preparedness Evaluation Tool (DPET). The findings showed that most nursing students had a moderate level of perception regarding natural disaster management (85.8%). In specific phases, students demonstrated moderate perceptions in preparedness (66.7%), emergency response (92%), and recovery (76.4%). The study recommends that nursing education institutions in Padang City strengthen their curricula by integrating comprehensive disaster management content, implementing practical simulations, developing modules on post-traumatic stress disorder (PTSD) management, and establishing sustainable disaster preparedness programs to enhance student competence and readiness.